Methicillin- and Vancomycin-Resistant Staphylococcus aureus From Humans and Ready-To-Eat Meat: Characterization of Antimicrobial Resistance and Biofilm Formation Ability - Saber, Taisir; Samir, Mohamed; El-Mekkawy, Rasha M.; Ariny, Eman; El-Sayed, Sara Ramadan; Enan, Gamal; Abdelatif, Sawasn H.; Askora, Ahmed; Merwad, Abdallah M. A.; Tartor, Yasmine H. (Frontiers in Microbiology, 2022)
Methicillin-resistant and vancomycin-resistant Staphylococcus aureus (MRSA and VRSA) are zoonotic life-threatening pathogens, and their presence in food raises a public health concern. Yet, scarce data are available regarding MRSA and VRSA in both ready-to-eat (RTE) meat and food handlers. This study was undertaken to determine the frequency, antimicrobial resistance, and biofilm-forming ability of MRSA and VRSA isolated from RTE meat (shawarma and burger) and humans (food-handlers, and hospitalized patients) in Zagazig city, Sharkia Governorate, Egypt. We analyzed 176 samples (112 human samples: 72 from hospitalized patients and 40 from food handlers, 64 RTE meat samples: 38 from shawarma and 26 from burger). Using phenotypic, PCR-based identification of nuc gene and matrix assisted laser desorption ionization (MALDI) TOF mass spectrometry, 60 coagulase-positive S. aureus (COPS) isolates were identified in the samples as follow: RTE meat (15/64, 23.4%), hospitalized patients (33/72, 45.8%) and food handlers (12/40, 30%). All the COPS isolates were mecA positive (and thus were classified as MRSA) and multidrug resistant with multiple antibiotic resistance indices ranging from 0.25 to 0.92. Overall, resistance to cefepime (96.7%), penicillin (88.3%), were common, followed by ampicillin-sulbactam (65%), ciprofloxacin (55%), nitrofurontoin (51.7%), and gentamicin (43.3%). VRSA was detected in 30.3% of COPS hospitalized patients´ isolates, 26.7% of COPS RTE meat isolates and 25% of COPS food handler’s isolates. VanA, vanB or both genes were detected in 64.7%, 5.9%, and 29.4% of all VAN-resistant isolates, respectively. The majority of the COPS isolates (50/60, 83.3%) have biofilm formation ability and harbored icaA (76%), icaD (74%), icaC (50%), and icaB (46%) biofilm-forming genes. The bap gene was not detected in any of the isolates. The ability of MRSA and VRSA isolates to produce biofilms in addition to being resistant to antimicrobials highlight the danger posed by these potentially virulent microorganisms persisting in RTE meat, food handlers, and patients. Taken together, good hygiene practices and antimicrobial surveillance plans should be strictly implemented along the food chain to reduce the risk of colonization and dissemination of MRSA and VRSA biofilm‐producing strains.